An asthma self-management program based on WeChat to improve asthma control and quality of life: a randomized controlled trial - Shanshan Xu; Zhihui Song; Xiao Cheng; Jiawei Wang (Frontiers in Allergy)
BackgroundFew studies have tested the feasibility and efficacy of WeChat-based asthma self-management, which supports patients in managing their asthma via mobile phone. We developed an intervention program based on the WeChat Mini program to support self-management. We evaluated the effectiveness and feasibility of improving asthma control and quality of life in patients with asthma.MethodsFifty and 53 patients were randomized into the control and WeChat groups, respectively, to receive traditional interventions and interventions based on the WeChat Mini program. We conducted the intervention for three months and then observed for three months.ResultsAt the end of the third month, the Asthma Control Test (ACT) scores of the WeChat group were greater than those of the control group (P = 0.003), and the ACT scores of the two groups were significantly higher than those at baseline (P = 0.028; P < 0.001). At the end of the sixth month, the control group was not significantly different from the baseline group (P = 1.000), but the WeChat group was significantly different (P < 0.001). The ACT scores of the WeChat group were higher than those of the control group (P = 0.001). The ACT scores of the WeChat group were lower than those of the third month, but the difference was insignificant (P = 0.214). For asthma self-management and quality of life, the WeChat group improved more at the end of the third and sixth months (all P < 0.001).ConclusionImplementing an asthma self-management program based on the WeChat application is effective in helping patients with asthma improve their asthma control and quality of life.